2009
DOI: 10.1002/hed.21165
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the treatment of pain related to radiation‐induced mucositis in patients with head and neck tumors treated with intensity‐modulated radiation therapy

Abstract: Background. This retrospective study evaluates the efficacy of gabapentin for the treatment of pain syndrome related to radiation-induced mucositis in patients with head and neck tumors.Methods. Thirty cases of head and neck malignancies treated with radiotherapy were analyzed.Results. By using a median dose of 2700 mg/day of gabapentin, only 10% of patients required additional narcotic pain medications for adequate pain relief during the third and fourth week of treatment, despite grade 2 or higher mucositis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…The efficacy of gabapentin was assessed by examining the need for opioids for pain relief. The authors concluded that gabapentin can provide pain relief and reduce the need for opioids [5,6]. No guideline was possible due to insufficient evidence.…”
Section: Gabapentinmentioning
confidence: 99%
“…The efficacy of gabapentin was assessed by examining the need for opioids for pain relief. The authors concluded that gabapentin can provide pain relief and reduce the need for opioids [5,6]. No guideline was possible due to insufficient evidence.…”
Section: Gabapentinmentioning
confidence: 99%
“…11 Prophylactic gabapentin can reduce the total opioid requirement and unintentional weight loss, delay feeding tube use, and decrease unplanned treatment breaks in patients undergoing CRT for HNC. [12][13][14][15][16] Combining gabapentin with opioids improves pain relief at lower opioid doses and improves daily activity, mood, sleep, and QOL in patients undergoing treatment for HNC. 17 To our knowledge, the dose response of gabapentin is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical implications of the results are that careful and repeated attention has to be directed to current and expected pain mechanisms. When systematic analgesics do not provide sufficient OM pain relief, we suggest, according to our very limited clinical experience and to the recent publication of Bar Ad et al (2009) [27], and in absence of other possibilities at present, that additional treatment with gabapentin or pregabalin might be tried. However, the effect of gabapentin and pregabalin on OM pain has to be evaluated in carefully designed studies.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 89%
“…We agree with the recent publications [3,11,25] suggesting use of adjuvant medication more frequently and earlier in OM development in order to attain improved pain relief. In a recent study Bar Ad et al (2009) [27] stated, that gabapentin appeared to be promising in reducing the need of opioids for patients with OM pain, which indicates that the role of gabapentin in OM pain therapy ought to be studied.…”
Section: Discussionmentioning
confidence: 99%